Analysis of the Due Diligence System of Australian Timber Legality Based on Standards of ISO Risk Management - Jang, E.K.; Seol, M. (Korean Society of International Agriculture, 2021)
Global society has been putting efforts together to prevent forests from rampant deforestation and illegal logging worldwide since sustainability is a common goal for the Earth. At the World Summit on Sustainable Development (WSSD) called Rio+10, global efforts of timber importing countries and private sectors to restrain illegal logging were discussed in 2002. As a market instrument to eradicate illegal logging, timber legality systems in consumer countries have been implemented, starting with the United States since 2008, the European Union (EU) since 2013, Indonesia since 2016, Australia since 2017, Japan since 2018, and the Republic of Korea since 2019. In the implementation stage of the timber legality, the due diligence system plays a role in reducing the risk of illegally logged timber in a supply chain. This study investigated the due diligence system of Australian timber legality as a good practice and analyzed it according to the standard of risk management of International Standard Organization (ISO) consisting of 1) risk identification, 2) risk analysis, 3) risk assessment, 4) risk treatment, and 5) monitoring and review. As a result, the due diligence system of Australia was compatible with the risk management criteria of ISO. The timber legality in Australia was established based on relevant laws and regulations. Its system stepwise was composed of risk assessment and mitigation as well as risk identification and analysis of illegal logging possibility in accordance with origins and species. Eventually, this study clarified the structure of due diligence systems and evaluated the crucial points of these systems based on standards of ISO risk management. Results of this study will contribute to our understanding of timber legality towards sustainable development.